The use of mind mapping strategy to improve speaking competency among EFL primary school students - Nur Salina, Ismail; Ansar, AlWadi (2019)
The goal of learning the English language is the ability to communicate in the language. Thus, teaching and learning of speaking is an indisputable requirement in the English Language as a foreign language classroom. However, EFL students have problems with spoken English, may be as a result of poor motivation to speak the language, language anxiety, or lack of effective teaching and learning strategies. In order to broaden the understanding of the way to improve speaking competency among EFL students, this conceptual paper attempts to examine the application of the mind mapping strategy to improve speaking competency among EFL primary school students through a critical analysis of the related literature by addressing the following research questions; what are the problems and difficulties that EFL students face while they are speaking in the classroom? And to what extent does the use of mind mapping strategy help to improve EFL students’ speaking skills in the classroom? Based on embedding theories and previous studies concerning the use of mind mapping strategy in speaking activities, this paper offers great practical guidance on the contextualization of the mind mapping strategy and recommendations for its future as an effective strategy to improve speaking’ competency in the classroom.